Manajemen Koleksi Perpustakaan UHW Perbanas Surabaya - Dio Eka Prayitno; Reza Mua'dzatul Masrurah (Central Library of Universitas Sebelas Maret, 2022)
Good collection management is also good information management. Collections are also a key factor in determining user satisfaction, therefore collections need to be developed. The purpose of writing this article is a best practice carried out by the University of Hayam Wuruk Perbanas which can be an illustration or an addition to the treasures of knowledge in the world of libraries, especially in terms of collection development. This writing method uses a literature study. Up-to-date information in a library is an important thing and must be done in order to preserve information and develop knowledge. This cannot be separated from the use of information and communication technology (ICT) which is applied in the library. Collection of library materials is an embodiment of the information preservation process. Collection development carried out by libraries is a very important process because in these activities, libraries involve users and leaders or stakeholders. The collections owned must be in accordance with the needs of users and the direction of the purpose of the formation of the library itself. So it is necessary to develop a library collection management that can meet the needs of users. Collection development needs to be carried out on an ongoing basis so that users can use the library continuously so that dependence on the library arises. The collection development process consists of analyzing user needs, selecting library material collections, holding library materials, conducting stock taking, maintaining library materials and weeding. This is done as an effort to maintain the up-to-date information contained in the library because the main purpose of a library is to be a user. From the results of the discussion writer concludes that the collections owned by the Hayam Wuruk Library at Perbanas Surabaya are in accordance with the needs of users. Keywords: collection management; collection development; library collection